1980
DOI: 10.1093/nar/8.20.4777
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bisulfite modification of 5-methyldeoxycytidine and deoxycytidine residues

Abstract: Sodium bisulfite is a mutagen which can specifically deaminate more than 96% of the cytosine residues in single-stranded DNA via formation of a 5,6-dihydrocytosine-6-sulfonate intermediate. Under the same reaction conditions, only 2-3% of the 5-methylcytosine (m5Cyt) residues in single-stranded XP-12 DNA, which has 34 mole% m5Cyt, was converted to thymine (Thy) residues. In contrast, at the deoxynucleoside and free base levels, the same treatment with bisulfite and then alkali converted 51% and > 95%, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
127
0
4

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(134 citation statements)
references
References 23 publications
(35 reference statements)
1
127
0
4
Order By: Relevance
“…Previous studies reported p15 gene methylation in 18-60% of ALL patients (Wang et al, 1980;Iravani et al, 1997;Chim et al, 2001;GarciaManero et al, 2002b;Chim et al, 2003;Garcia-Manero et al, 2003;Roman-Gomez et al, 2004;Scott et al, 2004;Canalli et al, 2005;Roman-Gomez et al, 2005;Takeuchi et al, 2012). In contrast to these studies, Chen and Wu (2002) reported methylation in 90% of ALL patients, while Matsushita et al (2004) reported absence of p15 methylation.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies reported p15 gene methylation in 18-60% of ALL patients (Wang et al, 1980;Iravani et al, 1997;Chim et al, 2001;GarciaManero et al, 2002b;Chim et al, 2003;Garcia-Manero et al, 2003;Roman-Gomez et al, 2004;Scott et al, 2004;Canalli et al, 2005;Roman-Gomez et al, 2005;Takeuchi et al, 2012). In contrast to these studies, Chen and Wu (2002) reported methylation in 90% of ALL patients, while Matsushita et al (2004) reported absence of p15 methylation.…”
Section: Discussionmentioning
confidence: 92%
“…25 For bisulfite treatment, 1 g of genomic DNA was denatured by NaOH and modified by sodium bisulfite, which converts all unmethylated cytosines to uracil while methylated cytosines remain unchanged. 26 The modified DNA was purified using a Wizard DNA purification kit (Promega, Madison, WI), treated with NaOH to desulfonate, precipitated with ethanol, and resuspended in water.…”
Section: Dna Extraction and Bisulfite Treatmentmentioning
confidence: 99%
“…Treatment with sodium bisulfite can be used to convert methylated and unmethylated DNA to different sequences [9,10] (Fig. 1a).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%